REMOVAL OF HEAVY METAL IONS IN WATER USING MODIFIED POLYAMIDE THIN FILM COMPOSITE MEMBRANES - Ngo, Thu Hong; Tran, Dung Thi (MATTER: International Journal of Science and Technology, 2017)
Heavy metals in the wastewater can pollute the water resources because they are durable, have a high toxicity in the environment and body tissues. Thus, the treatment of wastewaters containing heavy metal ions has attracted much attention, because they can economically provide water for industrial production, decrease the wastewater discharge amount, and minimize the effluent pollutant concentration. In some methods for treatment of heavy metal ions, membrane separation is considered as a great promise technique, because of their high efficiency, easy operation, and space saving. The commercial thin film composite polyamide (TFC-PA) membranes are used for the wastewater treatments, due to a high permeate flux, as well as a great rejection for relatively wide operation of temperature and pH range. However, TFC-PA membranes are sensitive to fouling. The improvement of the fouling resistance of TFCPA membrane can be achieved through the surface modification techniques. In this work, the surface of TFC-PA membrane has been successfully modified by the UV-photo-induced grafting of poly(ethylene glycol) (PEG) and acrylic acid (AA). The separation performance of the modified membranes has been investigated, through the possibility for removal of heavy metals such as Ni (II), Cu (II), Fe (III) and Cr (III) in water, and in electroplating wastewater. The experimental results indicated that the separation performance of the PEG-grafted and AAgrafted membranes is significantly improved, with an increased membrane flux at a great retention. The antifouling property of the modified membrane is also improved, with a higher maintained flux ratio, and a lower irreversible fouling factor in comparison with those of the unmodified one.